INOVASI PEMBELAJARAN BERDIFERENSIASI BERBASIS PROJECT PADA MATA PELAJARAN SEJARAH DI SMAN 1 DEPOK - Marta, Nur Aeni; Abrar, Abrar; Djunaidi, Djunaidi; Husmiati, Ratu (Universitas Sultan Ageng Tirtayasa, 2024)
The way history is taught in high school (SMA) still has some challenges. For instance, it is often text-heavy and focused on the teacher. Moreover, all students are given the same assignments regardless of their learning style. This can be demotivating and lead to boredom, resulting in a decline in student performance. To address this, innovative approaches to history teaching are needed. This article presents prototype examples of project-based learning steps that are tailored to students' needs, interests, and talents. The study used a qualitative method, including observation, interviews, and questionnaires. The data were analyzed using the ADDIE model, which is based on project-based learning. The results indicated that 89% of students were able to explore their talents and interests, and 97% of students were able to develop their skills. Project-based differentiated learning is an effective strategy for improving student learning outcomes by catering to their diverse cognitive needs.